Scientific Support of Occupational Risk Management Decisions in Industrial Sectors in Case of Uncertainty International - Kruzhilko, O. Ye.; Mahmoud, A. E. D.; Maystrenko, V. V.; Volodchenkova, N. V.; Polukarov, O. I.; Sydorenko, V.; Arlamov, O. O.; Кружилко, О. Є.; Майстренко, В. В.; Володченкова, Н. В. (Occupational Health and Safety Society of Nepal (OHSSN), 2023)
One of the most important steps in risk assessment is the selection of assessment methods. Traditionally, when developing measures to reduce the level of occupational morbidity and industrial injuries, the results of an analysis of the causes, types of events and other factors that led to accidents are used. But such an approach does not meet modern requirements. For an adequate assessment of occupational risks, it is necessary to have objective data from different time periods: the onset of traumatic events in the past, the current state of threats to life and health of people, and the future state of threats in industrial sectors.
Keywords: Occupational risk; Algorithm; Mathematical model; Expert method; Environmental health